MULTIMODAL DISCOURSE ANALYSIS OF AN ENGLISH LANGUAGE LEARNING TEXTBOOK IN INDONESIA - Kaamilah Tafrijiyah; Merry Andriani (Elite Laboratory Jurusan Sastra Inggris Universitas Bangka Belitung, 2025)
This investigation scrutinizes linguistic and non-linguistic modes, through a multimodal discourse analysis, on the English textbook, entitled “Bahasa Inggris English for Change” (2022). This research delves into how social and cultural values applied in the English textbook have fulfilled the vision of the Indonesian education curriculum, which is to create Pancasila students (pelajar Pancasila), and also to appraise social and cultural components introduced in the textbook. The observed data are collected by using documentation technique and purposive sampling. Four analysis stages, involving a verbal analysis, visual analysis, spatial analysis, and gesture analysis, are carried out. The findings indicate that the English learning textbook strongly emphasizes local social and cultural principles, especially in its visuals. Furthermore, the literary texts and visual images in the English textbook have not been able to reflect the values of Pancasila specifically. The findings suggest Indonesian English teachers creatively strengthen the Pancasila values and global knowledge to learners through assignments outside the materials in the textbook.